Case Report: Guillain–Barré Syndrome Associated With COVID-19 - Khedr, Eman M.; Shoyb, Ahmed; Mohamed, Khaled O.; Karim, Ahmed A.; Saber, Mostafa (Frontiers in Neurology, 2021)
ABSTRACT Guillain–Barré syndrome (GBS) is a potentially fatal, immune-mediated disease of the peripheral nervous system that is usually triggered by infection. Only a small number of cases of GBS associated with COVID-19 infection have been published. We report here five patients with GBS admitted to the Neurology, Psychiatry, and Neurosurgery Hospital, Assiut University/Egypt during the period from first of July to 20 November 2020. Three of the 5 patients were positive for SARS-CoV-2 following polymerase chain reaction (PCR) of nasopharyngeal swabs and another one had a high level of Igm and IgG; all had bilateral ground glass appearance with consolidation on CT chest scan and lymphopenia. All patients presented with two or more of the following: fever, cough, malaise, vomiting and diarrhea. However, there were some peculiarities in the clinical presentation. First, there were only 3 to 14 days between onset of Covid-19 symptoms and the first symptoms of GBS which developed into a flaccid areflexic quadriplegia with glove and stocking hypoesthesia. The second peculiarity was that 3 of the cases had cranial nerve involvement, suggesting that there may be a high incidence of cranial involvement in SARS-CoV-2 associated GBS. Other peculiarities occurred. Case 2 presented with a cerebellar hemorrhage before symptoms of COVID-19 and had a cardiac attack with elevated cardiac enzymes following onset of GBS symptoms. Case 5 was also unusual in that onset began with bilateral facial palsy which preceded the sensory and motor manifestations of GBS (descending course). Neurophysiological studies showed evidence of sensorimotor demyelinating polyradiculoneuropathy suggesting acute inflammatory polyneuropathy (AIDP) in all patients. Three patients received plasmapheresis. All of them had either full recovery or partial recovery.